2018
DOI: 10.1016/j.ejvs.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Imaging in Vascular Graft Infection: A Systematic Review and Meta-Analysis

Abstract: This meta-analysis suggests the diagnostic performance of WBC scintigraphy combined with SPECT/CT is the greatest in diagnosing VGI. However, it is a time consuming technique and not always available. Therefore FDG-PET/CT may be favourable as the initial imaging technique. The use of solitary CTA in diagnosing VGI seems to be obsolete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 27 publications
1
55
0
Order By: Relevance
“…6 Recent evidence-based articles have demonstrated the overall good diagnostic performance of 18 F-FDG PET or PET/CT for the diagnosis of vascular graft infection, including AGI (Table 1). [7][8][9] All the published meta-analyses are concordant about the high sensitivity and reasonable specificity of 18 F-FDG PET or PET/CT in this setting, independently from the different image analysis (qualitative or quantitative) used for the diagnosis, but false positive and false negative results should be taken into account. [7][8][9] In particular, reactive 18 F-FDG uptake in inflammatory cells around the vascular graft can mimic infection and it is a well-known confounder of 18 F-FDG PET image interpretation, in particular in cases of recent surgery.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…6 Recent evidence-based articles have demonstrated the overall good diagnostic performance of 18 F-FDG PET or PET/CT for the diagnosis of vascular graft infection, including AGI (Table 1). [7][8][9] All the published meta-analyses are concordant about the high sensitivity and reasonable specificity of 18 F-FDG PET or PET/CT in this setting, independently from the different image analysis (qualitative or quantitative) used for the diagnosis, but false positive and false negative results should be taken into account. [7][8][9] In particular, reactive 18 F-FDG uptake in inflammatory cells around the vascular graft can mimic infection and it is a well-known confounder of 18 F-FDG PET image interpretation, in particular in cases of recent surgery.…”
mentioning
confidence: 90%
“…[7][8][9] All the published meta-analyses are concordant about the high sensitivity and reasonable specificity of 18 F-FDG PET or PET/CT in this setting, independently from the different image analysis (qualitative or quantitative) used for the diagnosis, but false positive and false negative results should be taken into account. [7][8][9] In particular, reactive 18 F-FDG uptake in inflammatory cells around the vascular graft can mimic infection and it is a well-known confounder of 18 F-FDG PET image interpretation, in particular in cases of recent surgery. [7][8][9] Interestingly, it has been demonstrated that the combination of 18 F-FDG PET/CT reduces the false positive and false negative results compared to 18 F-FDG PET only.…”
mentioning
confidence: 90%
See 3 more Smart Citations